The Impact of Good Governance Implementation, Competency of Village Apparatus, and Internal Control Systems on Village Fund Management with the Utilization of Information Technology as a Moderating Variable - Wulan Sekar Ningsih; Taufeni Taufik; Suci Nurulita (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
Abstract This study aims to analyze the effect of the implementation of good governance, village apparatus competence, and internal control systems on village fund management, with the use of information technology as a moderating variable. This study is a quantitative study. The population in this study were all villages in the Rakit Kulim, Lubuk Batu Jaya, and Kuala Cenaku sub-districts totaling 38 villages. The sample used in this study was a saturated sample with a total of 152 respondents. The type of data used in this study was primary data and data collection techniques using questionnaires. The analysis method used was the Structural Equation Model using the Smart PLS program. The results of the study indicate that the implementation of good governance, village apparatus competence, and internal control systems partially affect the management of village funds. The use of technology does not moderate the implementation of good governance, village apparatus competence, on the management of village funds. The use of information technology moderates the internal control system on the management of village funds. This study has contributed to improving the management of village funds in the Rakit Kulim, Lubuk Batu Jaya and Kuala Cenaku sub-districts of Indragiri Hulu Regency